The challenges of women leaders of business organizations in Addis Ababa, Ethiopia, in balancing work-family responsibilities. - Bahiru, Bruktawit; Mengistu, Abeba Beyene (Journal of International Women's Studies, 2018)
Women's leadership significantly contributes to building high-performing organizations. However, challenges with balancing work and family responsibilities are inhibiting them from exerting their fullest potential towards this end. This study aims at investigating the challenges women leaders in Addis Ababa face in balancing the demands of their organizations with that of their families. A sample of eight women leaders of positions from large and middle scale organizations were taken using a purposive sampling technique. In-depth interviews were used to gather information for the study, and a phenomenological qualitative study was applied to analyze the data. The study identified some organizational, societal, and individual factors that challenge women leaders in balancing their work and family responsibilities. Work overload, cultural and social norms, family responsibilities, and upbringing related behaviors of the interviewees themselves were among the major challenges in maintaining their work-family balance. This study contributes insights into work-family balance theory and practice, by presenting women leaders' voices about their work-life challenges as expressed in their own words, from their own testimonies. It indicates that much needs to be done on the part of organizations, society, family, and women themselves for women leaders to have the desired level of work-family balance.
Keywords: 2000 à aujourd'hui; afrique; approches et analyses; conciliation famille-travail; discours dominant; famille; inégalités; projet charge mentale; périodes historiques; ressource en ligne; régions géographiques; systèmes d'oppressions; thématiques; travail; éthiopie

Pour une théorie générale de l'exploitation. Deuxième partie: repartir du bon pied - Delphy, Christine (Mouvements, 2004)
Keywords: OFDIG; afrique; amériques; approches et analyses; asie; cours; cycles supérieurs; discipline; discours dominant; exploitation; fem9000; intersectionnalité; marxisme; ressource en ligne; régions géographiques; sciences de la gestion; systèmes d'oppressions; thématiques; travail; violences; économie; économie sociale